2008
DOI: 10.1007/s11626-008-9122-0
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 185delAG truncation protein, BRAt, amplifies caspase-mediated apoptosis in ovarian cells

Abstract: Breast and ovarian cancer patients with germline mutations in BRCA1 respond more favorably to initial chemotherapy. We previously reported that cells from women carrying the BRCA1 185delAG founder mutation undergo an enhanced caspase-3-mediated apoptotic response. Here, we report on the transient and stable transfection of cDNA coding for the putative truncated protein product of the BRCA1 185delAG mutant gene into BRCA1 wild-type human ovarian surface epithelial cells and ovarian cancer cells, resulting in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…To rule out the possible contribution of wild‐type BRCA1 haploinsufficiency to altered apoptosis in 185delAG cells, BRAT was expressed in wild‐type BRCA1 ovarian surface epithelial cells. In agreement with our earlier studies, BRAT enhanced caspase 3‐mediated apoptosis and diminished levels of phospho‐Akt, cIAP1 and XIAP [46]. In more recent studies, we found that BRAT upregulated the expression of maspin [47], a tumor suppressor important in apoptosis, invasion and metastasis that is uniquely overexpressed in several tumor types, including ovarian cancer [48].…”
Section: Role Of Gain Of Function Mutations For Development Cellularsupporting
confidence: 92%
“…To rule out the possible contribution of wild‐type BRCA1 haploinsufficiency to altered apoptosis in 185delAG cells, BRAT was expressed in wild‐type BRCA1 ovarian surface epithelial cells. In agreement with our earlier studies, BRAT enhanced caspase 3‐mediated apoptosis and diminished levels of phospho‐Akt, cIAP1 and XIAP [46]. In more recent studies, we found that BRAT upregulated the expression of maspin [47], a tumor suppressor important in apoptosis, invasion and metastasis that is uniquely overexpressed in several tumor types, including ovarian cancer [48].…”
Section: Role Of Gain Of Function Mutations For Development Cellularsupporting
confidence: 92%
“…Previously, we demonstrated that human OSE cells with the BRAT mutation exhibited enhanced apoptosis and caspase-3 activation [ 11 ] as well as diminished levels of phosphorylated Akt, cellular inhibitor of apoptosis 1 (cIAP1), and X-linked inhibitor of apoptosis protein (XIAP) [ 12 ]. We also found that BRAT-mediated maspin expression was correlated with enhanced chemosensitivity [ 13 ] which is in agreement with clinical reports of increased survival in patients with elevated maspin levels [ 14 ]. Microscopic examination of ovarian specimens obtained following prophylactic oophorectomy from women with FH of OC indicated that greater than 85% presented with two or more abnormal OSE histologic features such as surface epithelial pseudostratification, surface papillomatosis, cortical invaginations of OSE, epithelial inclusion cysts, and epithelial hyperplasia [ 15 ].…”
Section: Introductionsupporting
confidence: 87%
“…The following SV 40-Large T-Antigen transfected human OSE (IOSE) cell lines were used: IOSE118 derived from a normal patient with a FH of breast and/or OC with wtBRCA1 status confirmed [ 13 ]; IOSE 121 derived from a normal patient with NFH of breast and/or OC though BRCA1 mutation status was not determined; and IOSE 3261-77 and IOSE 1816-686 derived from normal patients with a FH of breast and/or OC as well as confirmed carriers of the BRCA1 185delAG mutation. IOSE cells were cultured in Medium 199/MCDB 105 (Sigma, St. Louis, MO) with 10% fetal bovine serum (FBS) and gentamicin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations